A DNA‐Encoded Library of Chemical Compounds Based on Common Scaffolding Structures Reveals the Impact of Ligand Geometry on Protein Recognition. (1st June 2018) - Favalli, Nicholas; Biendl, Stefan; Hartmann, Marco; Piazzi, Jacopo; Sladojevich, Filippo; Gräslund, Susanne; Brown, Peter J.; Näreoja, Katja; Schüler, Herwig; Scheuermann, Jörg; Franzini, Raphael; Neri, Dario
Abstract: A DNA‐encoded chemical library (DECL) with 1.2 million compounds was synthesized by combinatorial reaction of seven central scaffolds with two sets of 343×492 building blocks. Library screening by affinity capture revealed that for some target proteins, the chemical nature of building blocks dominated the selection results, whereas for other proteins, the central scaffold also crucially contributed to ligand affinity. Molecules based on a 3, 5‐bis(aminomethyl)benzoic acid core structure were found to bind human serum albumin with a K d value of 6 nm, while compounds with the same substituents on an equidistant but flexiblel ‐lysine scaffold showed 140‐fold lower affinity. A 18 nm tankyrase‐1 binder featuredl ‐lysine as linking moiety, while molecules based ond ‐Lysine or (2 S, 4 S )‐amino‐l ‐proline showed no detectable binding to the target. This work suggests that central scaffolds which predispose the orientation of chemical building blocks toward the protein target may enhance the screening productivity of encoded libraries. Abstract : Phenylpropanoic acid‐derived PPAR agonist TIPP‐204, shows high selectivity for human (h)PPARδ while structurally related TIPP‐401 is a hPPARα/δ dual agonist. Computational docking of TIPP‐401 in the ligand binding domain (LBD) of hPPARα and hPPARδ, and inspection of the TIPP‐204–hPPARδ LBD co‐crystal structure identified key amino acids responsible for the differences in selectivity of the two analogues. These results were confirmed using mutagenesis assays. The amino acids determining the potency and selectivity of TIPP‐204 are different to those of the PPARδ‐ selective agonist GW‐501516, which belongs to a different chemical class.